MULTIMODAL METAPHOR IN ADVERTISEMENT - Nahdyah Sari Daulay; SitiIsma Sari Lubis; Widya Wulandari (Universitas Islam Sumatera Utara (UISU), 2018)
Metaphor based on the cognitive linguistic view can be defined as a tool which allows us to understand one conceptual domain in terms of another. What usually happens is that we use a physical. What we need to comprehend, is the target domain. It means that human cognition is organized in conceptual schema. Rodriguez (2015) stated that multimodal needs a mental comprehension process which differs from processing visual or verbal concepts alone. Metaphor has been used in many advertising. The metaphor can be interpreted differently from one to others. This paper was to present an analysis of visual metaphors, and to illustrate the existence of a possible of multimodal metaphors in advertising. Multimodal needs a mental comprehension process which differs from processing visual or verbal concepts alone. In this case this study only focuses on the analysis of multimodality metaphor which found in some advertisements. In analyzing the multimodal metaphors in commercial advertising, corpus private static adverts from the TV were selected. All of the pictures presented are a verbal part.